Using a computer to develop early communication skills - Teris K. Schery and Lisa C. O'Canngr (Journal of All India Institute of Speech and Hearing, 1970)
Vocabulary learning and usage, motivational behavior, and social and communication growth were measured for eight severely handicapped toddlers under two different intervention conditions: a computer-based approach and traditional, individual play-based language therapy. Interventions, individual play-based language therapy. Interventions were administered in random order by graduate students in speech pathology. Videotapes were coded for both communication attempts and behavioral indices of attention and motivation. Communication growth was assessed using a standard set of communication-related measures administered before the interventions, at mid-point between the two treatment regimes, and after the second intervention. Notable progress was evidenced in both training conditions.